Adenosine A2A Receptors and A2A Receptor Heteromers as Key Players in Striatal Function - Ferre, Sergi; Quiroz, Cesar; Orru, Marco; Guitart, Xavier; Navarro, Gema; Cortes, Antonio; Casado, Vicent; Canela, Enric I.; Lluis, Carme; Franco, Rafael (Frontiers in Neuroanatomy, 2011)
A very significant density of adenosine adenosine A2A receptors (A2ARs) is present in the striatum, where they are preferentially localized postsynaptically in striatopallidal medium spiny neurons (MSNs). In this localization A2ARs establish reciprocal antagonistic interactions with dopamine D2 receptors (D2Rs). In one type of interaction, A2AR and D2R are forming heteromers and, by means of an allosteric interaction, A2AR counteracts D2R-mediated inhibitory modulation of the effects of NMDA receptor stimulation in the striato-pallidal neuron. This interaction is probably mostly responsible for the locomotor depressant and activating effects of A2AR agonist and antagonists, respectively. The second type of interaction involves A2AR and D2R that do not form heteromers and takes place at the level of adenylyl-cyclase (AC). Due to a strong tonic effect of endogenous dopamine on striatal D2R, this interaction keeps A2AR from signaling through AC. However, under conditions of dopamine depletion or with blockade of D2R, A2AR-mediated AC activation is unleashed with an increased gene expression and activity of the striato-pallidal neuron and with a consequent motor depression. This interaction is probably the main mechanism responsible for the locomotor depression induced by D2R antagonists. Finally, striatal A2ARs are also localized presynaptically, in cortico-striatal glutamatergic terminals that contact the striato-nigral MSN. These presynaptic A2ARs heteromerize with A1 receptors (A1Rs) and their activation facilitates glutamate release. These three different types of A2ARs can be pharmacologically dissected by their ability to bind ligands with different affinity and can therefore provide selective targets for drug development in different basal ganglia disorders.